92.8k views
5 votes
-6 = 3х - бу4х = 4 + БуSolving systems of equations using substitution method

1 Answer

3 votes

-6 = 3x - 6y

4x = 4 + 5y

ok

x = (4 + 5y)/4

Substitution

-6 = 3[(4 + 5y)/4] - 6y

-6 = [12 + 15y]/4 - 6y

-6 + 6y = [12 + 15y]/4

-24 + 24y = 12 + 15y

24y - 15y = 12 + 24

9y = 36

y = 36/9

y = 4

x = (4 + 5(4))/4

x = [4 + 20)/4

x = 24/4

x = 6

Solution x = 6, y = 4

User Stockholmux
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.